2007
DOI: 10.1007/s00705-007-0965-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibody to hepatitis E virus among wild sika deer, Cervus nippon, in Japan

Abstract: We examined 976 sika deer serum samples, 159 liver tissue samples and 88 stool samples collected from 16 prefectures in Japan, and performed ELISA and RT-PCR assays to detect antibodies to HEV and HEV RNA, respectively. Although 25 (2.6%) of 976 samples were positive for anti-HEV IgG, the antibody titers were very low. The OD values ranged between 0.018 and 0.486, forming a single distribution rather than a bimodal distribution, suggesting that the antibody detected in this study was not induced by HEV infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 29 publications
5
35
1
Order By: Relevance
“…In Japan, the prevalence among deer seems to be generally low, and HEV RNA has never Yu et al (2007) been detected in deer samples from Japan in cross-sectional studies, only in the mentioned human-related case (Tei et al, 2003). In serological studies, only 2% of the Sika deer have been shown to be seropositive for HEV (Sonoda et al, 2004;Matsuura et al, 2007), whereas wild boar from the same areas had a 9% seroprevalence (Sonoda et al, 2004). In contrast, Tomiyama et al (2009) found a high HEV seroprevalence (35%) in wild Yezo-deer (C. nippon yezoensis) from Hokkaido, where human hepatitis E is most prevalent within Japan Tanabe et al, 2011).…”
Section: Cervidsmentioning
confidence: 88%
“…In Japan, the prevalence among deer seems to be generally low, and HEV RNA has never Yu et al (2007) been detected in deer samples from Japan in cross-sectional studies, only in the mentioned human-related case (Tei et al, 2003). In serological studies, only 2% of the Sika deer have been shown to be seropositive for HEV (Sonoda et al, 2004;Matsuura et al, 2007), whereas wild boar from the same areas had a 9% seroprevalence (Sonoda et al, 2004). In contrast, Tomiyama et al (2009) found a high HEV seroprevalence (35%) in wild Yezo-deer (C. nippon yezoensis) from Hokkaido, where human hepatitis E is most prevalent within Japan Tanabe et al, 2011).…”
Section: Cervidsmentioning
confidence: 88%
“…Foodborne transmission was described in Japan in patients infected after consumption of undercooked pig liver or meat from wild boar or deer [27][28][29]. This route of infection may occur also in Europe since HEV has been detected in commercial pig liver sold in groceries and there is a high HEV seroprevalence in many pig herds [30,31].…”
Section: Ab094267mentioning
confidence: 99%
“…Studies on wild sika deer ( Cervus nippon ) have detected low prevalence rates for HEV, which suggests that sika deer are accidental hosts for the virus ( 4 , 5 ), despite the transmission link discovered between them and HEV in Japan ( 3 ) that raised awareness of the possibility that game animals transmit HEV ( 2 ). In Europe, information about HEV infection in wild ruminants is limited to reports suggesting that roe deer ( Capreolus capreolus ) and red deer ( Cervus elaphus ) can act as HEV hosts ( 6 8 ).…”
mentioning
confidence: 99%